Penerapan Sistem Pendukung Keputusan Pemilihan Biji Kopi Berbasis Web Dengan Metode Image Processing Dan Simple Additive Weighting Guna Meningkatkan Kualitas Biji Kopi (Studi Kasus Jastro Kopi) - Wahyu Hidayat, Dimas; Haryono, Wasis (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The coffee industry in Indonesia continues to grow with coffee consumption reaching 1.2 million tons per year (AEKI, 2023). However, the conventional coffee beans selection process takes 1–1.5 hours per 1 kg of coffee beans and is prone to subjectivity. This study develops a web based decision support system (DSS) that integrates image processing methods for coffee bean visuals (color, size, uniformity) and the Simple Additive Weighting (SAW) method for objective quality evaluation. The implementation of the system at Jastro Kopi shows an average coffee bean quality of above 70%, with Garut Arabica varieties as the best beans (97.3%) and Lintong Arabica the lowest (90.8%). This system has been proven to speed up the selection process to 20–30 minutes, maintain quality consistency, and be an efficient solution for the coffee industry.